The incidence and triggers of adult-onset Guillain-Barré syndrome in southwestern Finland 2004-2013. - J.O.T Sipilä; M. Soilu-Hänninen (Wiley, 2025)
BACKGROUND AND PURPOSE:
A Swiss study recently reported surgery as a potential risk factor for developing Guillain-Barré syndrome (GBS). It was sought to establish this in the Finnish adult population.
METHODS:
Persons over 16 years of age who received a diagnosis of GBS in 2004-2013 were identified from the patient register of Turku University Hospital and their patient records were analyzed to identify possible triggers.
RESULTS:
A cohort of 69 adult patients with GBS (63.8% men) was identified giving an annual incidence of 1.82/100 000. Of these, four (5.8%) had experienced a surgical procedure during the preceding 6 weeks with a relative risk of 6.28 (95% confidence interval 4.15-9.47, P < 0.001) compared with the general study population or a risk of 1.25/100 000 operations. No difference between genders was found. Only two (2.9%) patients had received a vaccination [one against seasonal influenza (P = 0.888) and one against pandemic influenza (Pandemrix(®) , GlaxoSmithKline Biologicals, Rixensart, Belgium, relative risk 2.85, 95% confidence interval 1.27-6.38, P = 0.011)] during the preceding 6 weeks. The most common GBS triggers identified were respiratory tract infections in 30 cases (43.5%) and gastroenteritis in 16 cases (23.2%) whilst two patients (2.9%) had had both.
CONCLUSIONS:
The overall incidence of GBS in the adult population of southwestern Finland was similar to previous studies worldwide and the most common triggers were respiratory tract infections and gastroenteritis. Surgery was a rare risk factor and of vaccinations only the one against pandemic influenza raised the risk of GBS.